Moving to mobility : creating a successful remote work environment - Roseberry, Catherine (BSI, 2008)
This book provides remote work managers and remote workers with comprehensive guidance to make informed choices about the way they work, where they work and what equipment is best suited to fulfill their job functions.
Keywords: Telecommuting.; Teams in the workplace -- Computer networks.; Organizational effectiveness.; Personnel management.; elektronické knihy; electronic books